2015
DOI: 10.1007/s00701-015-2645-8
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of pharmacologically induced platelet dysfunction in the acute setting of brain injury

Abstract: Our results demonstrate the high frequency of pharmacologically impaired platelet function in patients with unknown preexisting medication. Early assessment of platelet function is an important tool to allow optimized treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
(38 reference statements)
0
14
0
1
Order By: Relevance
“…This latter effect has been considered to be mediated by nuclear factor kappa B (NF-κB) [264]. Although there is a potential risk of bleeding complications in a TBI situation when using ASA [265], the results of two studies showed no hazardous effects of ASA intake prior to injury [266,267].…”
Section: Acetylsalicylic Acid (Asa)mentioning
confidence: 99%
“…This latter effect has been considered to be mediated by nuclear factor kappa B (NF-κB) [264]. Although there is a potential risk of bleeding complications in a TBI situation when using ASA [265], the results of two studies showed no hazardous effects of ASA intake prior to injury [266,267].…”
Section: Acetylsalicylic Acid (Asa)mentioning
confidence: 99%
“…The results are expressed in the PRU (platelet reactivity unit) units showing the degree of aggregation mediated by P2Y12 receptors. [11,12,13] Acetylsalicylic acid irreversibly inhibits the COX-1 enzyme, then the synthesis of cyclic endoperoxides and all prostaglandins that result therefrom. The COX-1 inhibition inhibits the synthesis of thromboxane, and then prostacyclin and prostaglandin E2.…”
Section: Discussionmentioning
confidence: 99%
“…The Multiplate analyzer was also used by Prinz et al in 103 neurosurgical patients with various types of acute brain injury (TBI, ICH, and SAH). 46 Impaired platelet function was found in more than 50% of patients with unknown preinjury medication intake and this underscores the value of POC testing in patients unable to give adequate information regarding medication intake. This finding was also observed by Bachelani et al who used the VerifyNow test in 84 patients with TBI.…”
Section: Antiplatelet Agent Activitymentioning
confidence: 99%